162k views
1 vote
Factorise the following:

{3x}^(2) + 5x - 12


1 Answer

5 votes

Answer:

(x + 3)(3x - 4)

Explanation:

Given

3x² + 5x - 12

Consider the factors of the product of the coefficient of the x² term and the constant term which sum to give the coefficient of the x- term.

product = 3 × - 12 = - 36 and sum = + 5

The factors are + 9 and - 4

Use these factors to split the x- term

3x² + 9x - 4x - 12 ( factor first/second and third/fourth terms )

= 3x(x + 3) - 4(x + 3) ← factor out (x + 3) from each term

= (x + 3)(3x - 4)

Thus

3x² + 5x - 12 = (x + 3)(3x - 4) ← in factored form

User Nimer Farahty
by
5.2k points